Analisis Geometrik Landas Pacu Bandar Udara Mutiara Sis Al Jufri - Femilia Pabimbin Salle; Latif Budi Suparma; Suryo Hapsoro Tri Utomo (Journal of Civil Engineering and Planning (JCEP), 2021)
The increase in population and economy is in line with the demand for movement to palu area and also from Palu to other areas using air transportation. Mutiara Sis Al Jufri Airport is one of the gateways to Central Sulawesi. Therefore, runway pavements should be able to receive the largest planned aircraft from the farthest planned route. This study aims to analyze the geometric development of runway pavement of Mutiara Sis Al Jufri Airport. The process of geometric analysis of runways using the ICAO (International Civil Aviation Organization) method using Boeing 737-900 ER as a planned aircraft, the results of the analysis were then evaluated against the existing geometric conditions of runway pavement Mutiara Sis Al Jufri Airport. Based on the results of the analysis obtained the results of the length of the runway with boeing 737-900 ER planned aircraft of 3019 m. Therefore, it is necessary to development on the runway of Mutiara Sis Al Jufri Airport of 769 m in order to serve the plan aircraft optimally without any restrictions on the weight of the aircraft. At runway width, runway shoulder, runway strip, RESA and stopway do not need to be developed because it has met ICAO rules.